(untitled) (Comparative & International Education Series, 2021)
Chapter 11|14 pages From Oppression to Global Social Justice: Practitioners’ Responsibility to International Students in the US Community College By Tiffany Viggiano, Evelyn Vázquez, Ariadna I. López Damián In this chapter, we articulate rhetorical roots of oppressive conditions experienced by community college international students in the United States. We link these conditions to foreign-born status and global changes (specifically, the 2017 Travel Bans and 2020 COVID pandemic). Through a revisit of “The Others: Equitable Access, International Students, and the Community College,” we demonstrate that the pattern of paradoxical and transactional arguments recently observed on the national stage is not new, but rooted in institutional culture. Current global contexts and nascent critical international literature cast a new light on our previous conceptualization of practitioners’ rationales for the enrollment of international students on their campuses. When practitioners use the transactional rationales, like those identified in “Others,” to recruit international students, they contribute to oppressive conditions for international students. By doing so they facilitate, and reproduce, global social injustice. GET ACCESS